Empowering Teacher of Religious Education in Multicultural Society - M Muslih (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2017)
This paper revealed the result of research regarding the position of teacher, focusing on the importance of empowering teachers of religious education in a multicultural society, such as Indonesia. Methodologically, it is a qualitative undertaking of literary research. Employing the technique of content analysis this study scrutinized features of a multicultural society, an exemplary profile of teachers of religious education, as well as how to empower this kind of teacher in order to fit in with a diverse society. The findings of this research are, multicultural society can be understood as a society that consists of several cultural communities with their overlapping but distinct conception of the world, a system of meaning, values, forms of social organizations, histories, customs, and practices. The idealized profile of a teacher of religious education is a type of teacher who meets the certain qualifications prescribed by Islamic teachings and is guided by the law and regulation in Indonesia, in particular. Teacher of religious education has a very important role in preparing students to be good citizens in a multicultural society. Therefore the teacher of religious education must have an awareness that he or she is part of a multicultural society. The teacher should be empowered to instill in his or her students an inclusive religious understanding to make them tolerant and respectful of other people of different cultures and religions, which is essential in order to strengthen harmony and national unity.